Pelaksanaan Pendidikan dan Pelatihan Kepemimpinan Tingkat IV Dalam Rangka Meningkatkan Kinerja Pegawai (Studi Kasus Pada Badan Kepegawaian Daerah Kabupaten Nganjuk) - Ariyan Kusuma Wardani (Jurnal Administrasi Publik, 2014)
The implementation of education and training leadership level IV in order to increase performance employees (Study at Badan Kepegawaian Daerah Kabupaten Nganjuk): The charges will the slow the employee performance in providing services to the public, lazy, not disciplined at the time of the working hours, often play truant be culture in the practice of work PNS. So as to be a huge challenge for the government to remove the nature of the central and local bureaucrats urged the government to get organized themselves on performance employees. Performance improvement this is done through education and training leadership. One who withdraws to be researched is on the regional governments education and training done at the level of echelon IV or known by education and training leadership level IV. It is held also on BKD district nganjuk  aimed at improving the performance of employees in SKPD district nganjuk. Research purposes is analyze and describe the implementation of (Diklatpim level IV) to improve its performance nganjuk, employees in the county the consequences participants (diklatpim IV) to increasing its performance by function ( is expected ) and dysfunctional (not to be expected), and the obstacles BKD as well as a participant in the implementation of (diklatpim IV). This research using methods qualitative with a kind of descriptive. The focus of the study: ( 1 ) the exercise of the results of diklatpim IV in the regentcy of nganjuk, ( 2 ) the consequence participants (diklatpim IV) to increasing its performance by function ( is expected ) and dysfunctional ( not to be expected ), ( 3 ) the obstacles BKD and the participants in the implementation of diklatpim IV.   Keywords: The implementation of Diklatpim IV, participants Diklatpim IV, of Badan Kepegawaian Daerah   Abstrak: Pelaksanaan Pendidikan dan Pelatihan Kepemimpinan Tingkat IV Dalam Rangka Meningkatkan Kinerja Pegawai (Studi Kasus Pada Badan Kepegawaian Daerah Kabupaten Nganjuk): Adanya Tuduhan akan lambannya kinerja pegawai dalam memberikan pelayanan kepada masyarakat, malas, ketidaksiplinan pada saat jam kerja, sering membolos menjadi budaya dalam praktek kerja PNS. Sehingga menjadi tantangan besar bagi pemerintah untuk menghilangkan sifat tersebut diranah birokrat baik pusat maupun daerah mendesak pemerintah untuk berbenah diri pada kinerja pegawai. Peningkatan kinerja ini dilakukan melalui pendidikan dan pelatihan kepemimpinan. Salah satu yang menarik untuk diteliti adalah pada Pemerintah Daerah, pendidikan dan pelatihan yang dilakukan ialah pada jenjang eselon IV atau dikenal dengan pendidikan dan pelatihan kepemimpinan tingkat IV. Hal ini dilaksanakan pula oleh BKD Kabupaten Nganjuk yang bertujuan untuk meningkatkan kinerja pegawai di SKPD Kabupaten Nganjuk. Tujuan penelitian adalah menganalisis dan mendeskripsikan pelaksanaan diklatpim tingkat IV untuk meningkatkan kinerja pegawai di Kabupaten Nganjuk, konsekuensi peserta diklatpim IV terhadap peningkatan kinerjanya secara fungsional (diharapkan) dan disfungsional (tidak diharapkan), serta kendala yang dihadapi BKD maupun peserta dalam pelaksanaan diklatpim IV. Penelitian ini menggunakan metode kualitatif dengan jenis deskriptif. Fokus penelitian: (1) Pelaksanaan hasil diklatpim IV di Kabupaten Nganjuk, (2) Konsekuensi peserta diklatpim IV terhadap peningkatan kinerjanya secara fungsional (DIharapkan) dan disfungsional (tidak diharapkan), (3) Kendala yang dihadapi BKD dan peserta pada pelaksanaan diklatpim IV.   Kata kunci: Pelaksanaan Diklatpim IV,  Peserta Diklatpim IV, Badan Kepegawaian Daerah